APPLE SCAB EARLY STAGE RECOGNITION USING RGB COLOR MODEL FILTERS - Orenīts, Kārlis; Šaicāns, Edgars; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The goal of the study is to develop a RGB color model filter that helps highlighting apple scab in its early stages. It is necessary to identify the apple scab because understanding the problem early can save the apple tree from getting damaged further. Images of apple scab were modified by zooming them in, adding artificial color, analyzing the RGB histograms. With this data authors were able to filter colors with specific values.